The Political Economy of European Populism: Labour Market Dualisation and Protest Voting in Germany and Spain - Dustin Voss (London School of Economics and Political Science (LSE), European Institute, 2018)
Many advanced economies around the world have recently witnessed a notable rise in populism stirring severe political unrest and social instability. This paper addresses the apparent academic confusion regarding the origins of this phenomenon and combines politico-economic analysis with electoral data to derive a new theory of populist demand. I conceptualise populism as a problem of political alienation stemming from the incapacity of social democratic parties to comprehensively represent the working class in the context of increased labour market dualisation. If the group of underrepresented workers is not sufficiently numerous to be electorally-relevant, right-wing populist protest parties can make use of the representational vacuum by reframing class-distributional issues along cultural conflict lines. If, however, the group of marginalised workers is large enough to mobilise political attention, left-wing populist parties will address socio-economic issues more directly. I thus assume an inverted hyperbolic causal relationship between labour market segmentation and the demand for populism. This hypothesis is tested in a critical case study on the electoral effects of labour market reforms in Germany and Spain.
Keywords: 330; populism; right-wing parties; dualisation; labour market reform; political representation